What was the cause of Friedrich Nietzsche's illness? - Žilinskas, E. (Neurologijos seminarai, 2023)
Background. Friedrich Nietzsche (1844-1900) is one of the most profound modern philosophers. Since childhood, Nietzsche suffered from severe headaches, and at the age of thirty he became blind in his right eye. At the age of 44, Nietzsche experienced a mental collapse, after which he became dependent on others. For a long time, it was thought that neurosyphilis was the diagnosis of Nietzsche's symptoms. However, latest studies suggest other hypotheses.Materials and methods. Nietzsche's letters to his friends, the memories of his family members and friends, and the medical records of his doctors were analysed. On the basis of primary sources, a retrospective medical history of Nietzsche is presented. Furthermore, in accordance with secondary articles on Nietzsche's illnesses, the main hypotheses have been provided along with their advantages and disadvantages.Results. The hypothesis of neurosyphilis becomes obsolete. New diagnoses have been proposed: frontotemporal dementia, intracranial mass, MELAS syndrome, and CADASIL.Conclusions. Despite a detailed analysis of Nietzsche's illnesses, the exact diagnosis remains unclear.
Keywords: CADASIL; MELAS; frontotemporal dementia; Nietzsche; neurosyphilis